2021
DOI: 10.15244/pjoes/139380
|View full text |Cite
|
Sign up to set email alerts
|

Combining Multi-Indices by Neural Network Model for Estimating Canopy Chlorophyll Content: a Case Study of Interspecies Competition between <i>Spartina alterniflora</i> and <i>Phragmites australis</i>

Abstract: The invasive species Spartina alterniflora show a significant coexistence zonation pattern with local Phragmites australis in different mixture ratio, increasing the difficulty to monitor their distribution directly by remote sensing. Canopy chlorophyll content (CCC) is an important indicator to monitor the growth and physiological status. The objective of this study was to estimate CCC under different mixture ratio. Five spectral indices were selected and combined via back propagation (BP) neural network mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Despite the considerable progress, the literature [6] points out that neither single feedforward nor recurrent neural network models can achieve satisfactory results for production processes with complex characteristics. In the literature [7], in recent years, it was found that deep learning spatio-temporal fusion soft measurement modeling that considers both temporal and spatial feature information can achieve improved measurement accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the considerable progress, the literature [6] points out that neither single feedforward nor recurrent neural network models can achieve satisfactory results for production processes with complex characteristics. In the literature [7], in recent years, it was found that deep learning spatio-temporal fusion soft measurement modeling that considers both temporal and spatial feature information can achieve improved measurement accuracy.…”
Section: Introductionmentioning
confidence: 99%